TEACHER'S EFFORTS TO INCREASE MOTIVATION OF STUDENTS' SPIRITUAL AND SOCIAL ATTITUDES IN SMAN 1 SITUBONDO - Mohammad Firmansyah; Abdul Muis (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
research that has done in SMAN 1 Situbondo aim to describe comprehensively the teacher’s efforts of Islamic religion education to enhance student’s spiritual and social attitude. This research using qualitative research metodologhy and data collection technique by observation, interview, documentation. The data was analyzed by data reduction, display, as well as taking the result and verification technique. This research on the teacher’s efforts of Islamic religion education to enhance student’s spiritual and social attitude produced several findings are supervise student regularly, establish spiritual and social attitude through emotional quotient, giving assessment. Moreover avoid threat, sanctions, and bad comentar too. Using variety method, increase desire and interest more better, creating a condusive evironmental scene.